2019
DOI: 10.1039/c9sc02412c
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-like chiral cages for catalyzing enantio-selective supramolecular polymerization

Abstract: Chiral organic cages can assist enantio-selective supramolecular polymerization through a catalyzed assembly (catassembly) strategy, like chaperones assist the assembly of biomolecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 62 publications
(61 reference statements)
1
32
0
Order By: Relevance
“…7a–c and S34, ESI † ). 49 The diameters of nanotubes (4.1 nm) are consistent with the individual supramolecule S1 from the energy-minimized structure. In our previous work, we found that cuboctahedral structures were stacked in square faces through crystal structures, 42 so it is assumed that the hierarchical self-assembly of nanofiber structures is packed in the same way ( Fig.…”
Section: Resultssupporting
confidence: 62%
“…7a–c and S34, ESI † ). 49 The diameters of nanotubes (4.1 nm) are consistent with the individual supramolecule S1 from the energy-minimized structure. In our previous work, we found that cuboctahedral structures were stacked in square faces through crystal structures, 42 so it is assumed that the hierarchical self-assembly of nanofiber structures is packed in the same way ( Fig.…”
Section: Resultssupporting
confidence: 62%
“…Their scope encompasses applications ranging from molecular detection often related with medical diagnosis, [1] to the switching phenomenon in connection with molecular machines, [2] and chiral catalysis. [3] Such chiroptical sensors comprise a more or less open cavity, in which the higher the number of interactions between host and guest, the higher the specificity of the recognition event. [4] To this regard, 3D cage cavities are theoretically preferred over macrocyclic ones, [5] with size and shape being key factors to consider for an accurate chiral matching.…”
mentioning
confidence: 99%
“…These successes overturn a traditionally accepted precept that self-assembly based on imine bond and water are incompatible. We envision that future research would include i) using imine condensation for self-assembling molecules with biological functions, which might be used for applications in some challenging areas such as drug delivery [47,48] and selective recognition of biological targets [49,50] such as a specific type of sugar; ii) using iminecontaining cage molecules as a reaction vessel to catalyze [51][52][53][54][55] organic reactions, or a molecular container that stabilizes a labile guest. [56][57][58][59][60][61][62] The strategy of multivalence might also be applied to other dynamic covalent systems, such as boronic ester and metathesis of olefin and alkyne, to stabilize the molecular structure.…”
Section: Discussionmentioning
confidence: 99%